2021
DOI: 10.1186/s12936-021-03956-z
|View full text |Cite
|
Sign up to set email alerts
|

Baseline malaria prevalence and care-seeking behaviours in rural Madagascar prior to a trial to expand malaria community case management to all ages

Abstract: Background Integrated community case management of malaria, pneumonia, and diarrhoea can reduce mortality in children under five years (CU5) in resource-poor countries. There is growing interest in expanding malaria community case management (mCCM) to older individuals, but limited empirical evidence exists to guide this expansion. As part of a two-year cluster-randomized trial of mCCM expansion to all ages in southeastern Madagascar, a cross-sectional survey was conducted to assess baseline ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another possible major reason for delaying treatment could be the use of traditional medicine, as found in low to middle-income Asia–Pacific countries [ 25 ]. A study conducted in a rural area of Madagascar found that only 28.7% sought care, and most of them visited public health facilities 46.8%, followed by community healthcare volunteers 31.0% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible major reason for delaying treatment could be the use of traditional medicine, as found in low to middle-income Asia–Pacific countries [ 25 ]. A study conducted in a rural area of Madagascar found that only 28.7% sought care, and most of them visited public health facilities 46.8%, followed by community healthcare volunteers 31.0% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the hospital sentinel network, the annual incidence of malaria in hospitalized patients was 25.77 per 100,000 people. The annual incidence was much higher in the age group of children aged 5 to 14 years (45.33 per 100,000 people) and in the sub-humid bio-climate zone (110.99 per 100,000 people) [20]. Therefore, it is crucial to extend malaria prevention measures to all age groups (so far it concentrates on children ≤5 years), especially at the community-based health center level and to reinforce control strategies [21].…”
Section: Discussionmentioning
confidence: 91%
“…For instance, school-based programs or an expansion of the target age for passive malaria case management in the community might also be efficient ways to diagnose and treat malaria in older children and adolescents. Indeed, expanding the age of malaria community case management to individuals older than 5 years is part of the malaria operational plan in Madagascar and is currently being assessed in a separate cluster randomized trial [ 25 ].…”
Section: Discussionmentioning
confidence: 99%